ICTs for Climate Change Adaptation in Africa - Creech, Heather; Akoh, Ben; Parry, Jo-Ellen (World Bank, Washington, DC, 2014)
Like other regions of the world, Africa is beginning to experience the impacts of human-induced climate change. These observed changes in climate parameters have not occurred uniformly across Africa. Mitigation is concerned with reducing the level of greenhouse gas emissions in the Earth's atmosphere that are the principal causes of climate change. Adaptation is concerned not with prevention but, in the words of the intergovernmental panel on climate change, with adjustments in human and or natural systems to reduce adverse impacts or take advantage of opportunities that may arise from it. Information and communication technology (ICT) have had an increasing impact on economic and social development over the past two decades, resulting from their capacity to generate and disseminate information, to facilitate the coordination of different actors in and beyond government, and to make government, business, and development processes more efficient. ICTs also have a complex relationship with sustainability and with the underlying cause of climate change. This relationship can be described in terms of the effects of ICTs: first order (direct) effects concern the impacts which ICTs have on climate change, in particular the carbon dioxide (CO2) emissions from the production, use and disposal of communications equipment and services, accounting for between 2 and 2.5 percent of global emissions. Second order (indirect) effects concern the role ICTs can play in reducing emissions resulting from other industrial sectors, by adopting ICTs to improve efficiency and production. Third order (societal) effects result from large-scale changes in social and economic behavior resulting from widespread use of ICTs, including changing patterns of trade, production and consumption, and global to local engagement of citizens in decision making.